(untitled) (Journal of Laboratory Animal Science, 2025)
Laboratory animals are the most widely established species in numerous fields for studying and developing new drug molecules and toxicity testing. A disproportionate number of animals are euthanized in the drug development and research field for societal benefit. In order to reduce the number of laboratory animals, a precise in vivo assessment system is essential to obtain statistically significant data. The project was initiated to evaluate vital organ function by utilizing nuclear medicine imaging techniques and radiopharmaceuticals. In this study, six mature rabbits (8-9 months old) of both sexes were systematically evaluated for vital organs like the brain, thyroid gland, salivary gland, heart, lung, liver, kidney function, skeletal system, and lymphatic system using organ-specific radiopharmaceuticals with scintigraphy and PET-CT imaging techniques. A detailed assessment of the function of each organ in rabbits was undertaken. No abnormalities were observed in the study animals under investigation. The uptake and clearance pattern of radiopharmaceuticals determined the normal organ function of rabbits and was found to be comparable with humans. In vivo, analysis with data generation was conceivable without sacrificing animals. Henceforth, by applying the 3Rs principle, the reduction and refine procedure is accomplished with a significant amount of critical data generated against each time point. Therefore, applying imaging techniques with the “3RS” principle proves to be an efficient method for rational use of laboratory animals during the investigation.